Effect of ozonation on the phytochemicals of black seed oil and its anti-microbial, anti-oxidant, anti-inflammatory, and anti-neoplastic activities in vitro - Aisha M. H. Al-Rajhi; Tarek M. Abdelghany; Mohammed S. Almuhayawi; Mohammed H. Alruhaili; Amna A. Saddiq; Afra M. Baghdadi; Soad K. Al Jaouni; Hibah M. Albasri; Moayad S. Waznah; Faisal A. Alraddadi; Samy Selim (Scientific Reports)
Abstract Black seed has been applied for several decades to cure an extensive variety of illnesses and ailments. In this report, the chemical profile of both crude and ozonized black seed oil was assessed after the oil was exposed to 0 to 5 L/minute of ozone for four hours. The in vitro effects of black seed oil following being exposed to ozone including antimicrobial properties versus Bacillus cereus (ATCC11778), Staphylococcus aureus (ATCC6538), Escherichia coli (ATCC8739), Salmonella typhi (ATCC 6539), and Klebsiella pneumoniae (ATCC13883), Candida albicans (ATCC10221), and Aspergillus niger (ATCC16888). Besides, antioxidant effects, anti-inflammatory capacity, and antineoplastic function versus HCT cells were assessed. The chemical profile of ozonized black seed oil showed elevation of essential molecules of oil as well as presence of some characteristic molecules to both forms of oil. Besides, it could be noticed that exposing of oil to ozone improves its antimicrobial activity towards all tested microbes except for C. albicans. Both forms of oil showed no activity towards A. niger. Black seed oil exposed to ozone showed a promising antioxidant capacity with IC50 of 2.93 ± 0.2 µg/ml. A dramatic improvement in anti-inflammatory impact of ozonized oil as well as its antitumor capacity towards HCT cells could be seen in the laboratory outcomes. The current findings point to a novel method for enhancing some of the in vitro medicinal uses of black seed oil by exposing it to ozone.